A história (ocidental) em tempos de mudança inaudita - Durão Rodrigues da Cunha, Marcelo (Revista de Teoria da História, 2021)
Resenha de: SIMON, Zoltán Boldizsár. History in Times of Unprecedented Change: A Theory for the 21st Century. Bloomsbury Publishing, 2019.